Seroprevalence of H. pylori Infection Among Anemic Patients in Tarhuna City - Fathi Albashir Hasan; Jamal Mahmoud Alayadi (African Journal of Advanced Pure and Applied Sciences, 2026)
Background: Anemia, particularly iron deficiency anemia, is a significant global health problem. While various factors contribute to its etiology, recent evidence suggests a strong association with Helicobacter pylori infection [1-3]. This study aimed to determine the seroprevalence of H. pylori in a population and to assess the association between H. pylori infection and anemia. Methods: A total of 100 participants were enrolled in a cross-sectional study. The population was divided into two groups: an anemic group (n=21) and a non-anemic group (n=79). The presence of H. pylori infection was determined by detecting H. pylori IgG antibodies in serum [12,13]. A Chi-square test was performed to evaluate the statistical significance of the association between H. pylori seropositivity and anemia status, with a significance level set at p<0.05 [7,8]. Results: The overall seroprevalence of H. pylori was 55% (n=55). A significantly higher seroprevalence was found in the anemic group (85.7%, n=18) compared to the non-anemic group (46.8%, n=37) [7]. The association between H. pyloriseropositivity and anemia was found to be statistically significant (χ²(1) = 11.83, p<0.001) [7,8]. Conclusion: This study demonstrates a strong and highly significant association between H. pylori infection and anemia [6,7,8]. The findings suggest that H. pylori is a major risk factor for anemia.